Morphological and molecular description of a novel species of Eimeria (Apicomplexa) that infects extraintestinal tissues of kiwi (Aves: Apteryx spp.) - Emma Scheltema; Kerri Morgan; Preet Singh; Barbara Adlington; Laryssa Howe (Systematic Parasitology, 2025)
Coccidia (Apiconmplexa) are naturally occurring and occasionally detrimental parasites of kiwi ( Apteryx spp.), a unique, flightless bird species dependent upon conservation efforts for survival. Using morphological and molecular data, a new coccidia species, Eimeria koka n. sp. , isolated from two closely related but geographically isolated kiwi host species, Apteryx rowi Tennyson et al. (rowi) and Apteryx mantelli Bartlett (North Island brown kiwi), is described. Oocysts are oval (20.8 × 15.9 μm) with a mean L/W ratio of 1.3, and a distinctive rough, crenellated brown oocyst wall (mean 1.2 μm), an oocyst residuum, 1–2 polar granules, and no micropyle. Sporocysts are ellipsoidal (11.6 × 6.3 μm) with a Stieda body and sporocyst residuum. Phylogenetic analysis of the cytochrome C oxidase subunit 1 (CO1) placed E. koka n. sp. in a separate clade to other Eimeria species previously identified from kiwi (Coker et al., Syst Parasitol 100(3):269–281, 2023). Comparison of DNA from oocysts with infected tissues from a single juvenile North Island brown kiwi confirmed parasitism of the kidney and lung tissues. This is the first Eimeria species identified from extraintestinal tissues in kiwi. Further molecular studies are recommended to determine the tissue distribution of E. koka n. sp. and other Eimeria species in kiwi.

Molecular characterisation and additional morphological descriptions of Eimeria spp. (Apicomplexa: Eimeriidae) from brown kiwi (Apteryx mantelli Bartlett) - Sarah M. Coker; Kate McInnes; Emilie Vallee; Patrick Biggs; William E. Pomroy; Laryssa Howe; Kerri J. Morgan (Systematic Parasitology, 2023)
Brown kiwi ( Apteryx mantelli Bartlett), a ratite endemic to New Zealand, is currently listed as “Vulnerable” under the IUCN classification system due to predation by introduced mammals. Operation Nest Egg (ONE) raises chicks and juveniles in predator-proof enclosures until they are large enough to defend themselves. These facilities experience an environmental accumulation of coccidial oocysts, which leads to severe morbidity and mortality of these kiwi. Four species of coccidia have been morphologically described from sporulated oocysts with additional opportunistic descriptions of endogenous stages. This research continues the morphological descriptions of these species of Eimeria with an additional novel morphotype also morphologically described. It also provides the first genetic characterisation targeting the mitochondrial cytochrome c oxidase I (COI) gene. Based on these findings, it was determined there are at least five morphotypes of Eimeria that infect brown kiwi and co-infections are common at the ONE facilities surveyed. The COI amplicon targeted for this study was sufficient to provide differentiation from other members of this genus. Sanger sequencing yielded ambiguous bases, indicating the need for more in-depth sequencing.